Reinvestment intentions in cryptocurrency: Examining the dynamics of risks and investor risk tolerance - Ishtiaq Ahmad Bajwa (Digital Business)
Digital currencies, including Bitcoins, Ethereum, and others, are an established alternative asset class opted by individual and institutional investors worldwide. However, this digital asset class carries several inherent risks. This study investigates the influence of three key risks, including liquidity risk, cyber risk, and regulatory risk, on the reinvestment intentions of investors. Data was collected from global crypto investors via a questionnaire and analyzed using PLS structural equation modeling. The study further used Investors' risk tolerance as a moderating variable. The findings of the study reveal that a significant and negative relationship exists between liquidity risk, cyber risk, regulatory risk, and investors' reinvestment intentions. Interestingly, investors with high-risk tolerance levels seem less affected by cyber security concerns, as they are more capable of absorbing or overlooking such risks. On the other hand, liquidity and regulatory risks appear to affect all types of investors irrespective of their risk tolerance level. This study bridges an important research gap by providing clear evidence on how these specific risks influence reinvestment decisions in the growing crypto market. It highlights the critical need for effective risk management strategies and stronger regulatory frameworks to address cyber vulnerabilities, tackle liquidity issues, and offer regulatory clarity. Taking these steps are essential for boosting investor confidence and encouraging their sustained involvement in the cryptocurrency ecosystem.